2018
DOI: 10.4314/jasem.v22i7.10
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Distribution Pattern of African Yam Bean (<i>Sphenostylis stenocarpa</i>) exposed to Cadmium stress

Abstract: In Nigeria, S. stenocarpa is an under-utilized leguminous crop grown in Edo State mainly for its tuberous root and less for the seeds. The purpose of this study was to determine the nitrogen assimilation and distribution pattern of S. stenocarpa exposed to cadmium stress by partitioning the plant accessions into root and leaf, and N-nitrate and N-ammonia analysis was carried out during the seedling and flowering stage. The results showed that cadmium stress increased percentage foliar total nitrogen in TSs-91 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…However, there is low awareness of its productive and nutritional value. Subsistence production may have been caused by the low acceptability of African yam bean as a valuable crop among middle-aged farmers in Africa [19][20][21]. It had its origin in Ethiopia but is now widely cultivated in tropical Africa, especially West Africa, in Cameroon, Ghana, and Nigeria [22].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is low awareness of its productive and nutritional value. Subsistence production may have been caused by the low acceptability of African yam bean as a valuable crop among middle-aged farmers in Africa [19][20][21]. It had its origin in Ethiopia but is now widely cultivated in tropical Africa, especially West Africa, in Cameroon, Ghana, and Nigeria [22].…”
Section: Introductionmentioning
confidence: 99%
“…Aside from its rich protein content, its high carbohydrate content [25,26] is comparable to the amount reported in grain cereals. A Review on the Cooking Attributes of African Yam Bean (Sphenostylis stenocarpa) DOI: http://dx.doi.org/10.5772/intechopen.99674 AYB's amino acid (histidine, isoleucine, lysine, methionine) profile is more in quantity than the amount observed in soybean [27][28][29]. Likewise, several authors have reported the presence of essential nutrients in AYB's seeds [25,26,[30][31][32][33][34][35][36].…”
Section: African Yam Beanmentioning
confidence: 99%
“…Biocharcoal proved to have ameliorative potential on AYB, however, more work is needed to understand the mechanism by which it operates. Ohanmu et al (2018) examined the nitrogen assimilation and distribution pattern of AYB exposed to cadmium stress by partitioning the plant accessions into root and leaf, and N-nitrate and Nammonia analysis was carried out during the seedling and flowering stage. It was reported that Cd toxicity reduced the total nitrogen assimilation of AYB accessions.…”
Section: Toxicological Analysis Of Aybmentioning
confidence: 99%